EFEKTIVITAS STRATEGI BELAJAR GEOGRAFI SISWA SMA NEGERI 1 RAKIT KULIM PADA MASA PANDEMI COVID-19 DI KABUPATEN INDRAGIRI HULU PROVINSI RIAU - Gustiana, Melta; Ernawati, Ernawati (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
ABSTRACT This research aims to find out (1) the effectiveness of memorization learning strategies, (2) the effectiveness of elaboration learning strategies, (3) the effectiveness of organizing learning strategies, (4) the effectiveness of metcognitive learning strategies, (5) the effectiveness of affective learning strategies, (6) what learning strategies are appropriately applied by learners during the covid19 pandemic in Sma Negeri 1 Rakit Kulim. This type of research is quantitative descriptive research. The population in this study was all students of class XI IPS in State High School 1 Rakit Kulim. Determination of the sample using total sampling. The source of this research data comes directly from students of kela IX IPS. The data collection techniques used are questionnaires and documentation. The results of this study showed that: (1) Learning strategies by memorization were less effectively carried out in SMAN 1 Rakit Kulim by 50% or 13 learners expressed less effective, (3) Learning strategies by elaboration were less effectively carried out in SMAN 1 Rakit Kulim by 42% or 11 learners expressed less effective, (3) Learning strategies by effective arrangement were carried out in SMAN 1 Rakit Kulim by 73% or 19 learners were effective, (4) Learning strategies by effective metacognitive means are carried out in SMAN 1 Rakit Kulim by 50% or 13 learners declared effective, (5) Learning strategies by means of less effective affective strategies are carried out in SMAN 1 Rakit Kulim by 50% or 13 learners declared less effective, (6) Strategies that are right applied by learners in conducting geography learning in SMAN 1 Rakit Kulim i.e. organizing strategies with a percentage of 44%. Keywords: Effectiveness of Student Learning Strategies